IDENTIFIKASI PERBEDAAN STANDAR AKUNTANSI ASET TETAP ANTARA US GAAP DAN IFRS - Sururi . (Akademi Akuntansi YKPN Yogyakarta, 2010)
Understanding the accounting standards is a must to anyone interested or engaged in financial accounting, therefore when the international accounting standards or IFRS has commonly agreed to be applied, the accounting standards in some countries, which were previously refer to U.S. accounting standards or U.S. GAAP, some eventually convergenced to IFRS, unfortunately many users of standards fail to comprehend the standards. In general, the interest area of the standards are around the issues of definition, recognition, measurement, classification, reporting, and disclosure of financial transactions. Nevertherless, a number of practitioners and academicians in the accounting facing obstacles in understanding the substance of the both standards. This article was written to address the issues, particularly on the accounting standards of fixed assets.Keywords: financial accounting, accounting standards, US GAAP, IFRS